Analysis of key candidate genes and pathways of endometriosis pathophysiology by a genomics-bioinformatics approach. (3rd July 2019) - Zhang, Zhimin; Ruan, Lin; Lu, Mingxuan; Yao, Xiaoguang
Abstract: Endometriosis is a common disease in women, but the signaling pathways and driven genes involved remain unclear. This study integrated four datasets to elucidate potential key candidate genes and pathways in endometriosis. Four expression profile datasets including 29 endometriosis lesions and 37 normal tissues were integrated and analyzed. Differentially expressed genes (DEGs) were sorted, and the gene ontology, pathway enrichment, and protein–protein interaction network of candidate genes were then analyzed. A total of 94 shared DEGs were identified from the four datasets. The DEGs were clustered based on functions and signaling pathways through the analysis of significant enrichment. Among the DEG protein-protein interaction network complex, 87 nodes/DEGs were identified. Furthermore, 18 central node genes were identified, and most of the corresponding genes were involved in the angiotensin system, smooth muscle contraction, cell junction organization, and lipoxin pathways. Through integrated bioinformatic analysis, we identified candidate genes and pathways in endometriosis, which could improve our understanding of endometriosis.